Treatment of neurosarcoidosis: A comparative study of methotrexate and mycophenolate mofetil. (13th December 2016) - Bitoun, Samuel; Bouvry, Diane; Borie, Raphaël; Mahevas, Mathieu; Sacre, Karim; Haroche, Julien; Psimaras, Dimitri; Pottier, Corinne; Mathian, Alexis; Hie, Miguel; Boutin, Du Le Thi Huong; Papo, Thomas; et al.
Abstract : Objective: To compare the efficacy of methotrexate (MTX) and mycophenolate mofetil (MMF) in the prevention of relapses in neurosarcoidosis. Methods: We conducted a retrospective multicenter study including patients who received MTX or MMF for the treatment of histologically proven neurosarcoidosis. The efficacy of the immunosuppressive drug was assessed by determining the time to relapse. Results: Forty patients with a diagnosis of neurosarcoidosis (24 men, 16 women, median age at diagnosis 43.5 years) who received at least 3 months of MTX (n = 32) or MMF (n = 14) were included. The immunosuppressive drug was always associated with steroids. The rate of relapse was 47% in the MTX group (0.2 relapses per year of exposure) and 79% in the MMF group (0.6 relapses per year of exposure) ( p = 0.058). The median time to relapse was significantly shorter in the MMF group (11 months) compared with the MTX group (28 months) ( p = 0.049). Adverse events occurred in 11 patients during MTX therapy and in 1 patient during MMF therapy ( p = 0.12). Conclusions: Relapses of neurosarcoidosis occur frequently, despite the use of an immunosuppressive drug in addition to corticosteroids. MTX significantly increases the survival time without relapse compared to MMF and should be preferred over MMF for the treatment of neurosarcoidosis. This study provides Class IV evidence that for patients with neurosarcoidosis taking steroids, MTX is superior to MMF in reducing the risk of relapse.